Sliding Gate Opener System with Smartphone Control Using Bluetooth Connection - Budhi Anto; Amir Hamzah; Dahliyusmanto (International Journal of Electrical, Energy and Power System Engineering, 2023)
This paper presents the sliding gate opener system that android smartphones can remotely control using Bluetooth protocols. The gate opener is driven by a 12-pole single-phase induction motor of permanent-split-capacitor type (PSC motor) coupled with a worm gearbox and rack-pinion power transmission. The PSC motor installation is wired to rotate either forward or in the reverse direction by using a contactors arrangement controlled by the Arduino microcontroller module. Two limit switches are installed at the ends of the gate opener movement to inform the microcontroller to stop the motor automatically when the gate opener touches them. Moreover, the microcontroller module has been wired with Bluetooth transceiver HC-06 enabling it to communicate with other Bluetooth devices. The microcontroller module has been programmed so that the gate opener movement can be remotely governed from android smartphones and controlled at the site by operating a set of pushbutton switches mounted onto the control panel's door. The functional test has been conducted on the sliding gate opener system, and the result shows that the gate opener movement can successfully be controlled locally through operating pushbutton switches and remotely using an android smartphone with up to 8 meters.